Blended Learning Effectiveness and College Students’ Deep Learning Perceptions: The Community of Inquiry Perspective - Shen, Dandan; Chang, Chiung-Sui; Yang, Junjie (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2025)
Emerging technologies and innovative instructional methods have revolutionized education, making blended learning the new standard in the artificial intelligence era. However, poor integration of online and face-to-face learning has led to challenges such as superficial student engagement. This study developed a Community of Inquiry-based blended learning model and evaluated its effectiveness with 92 college students using a quasi-experimental approach. Over 16 weeks, the experimental group (n = 48) adopted the blended learning model, while the control group (n = 44) used traditional learning conditions. Learning effectiveness and deep learning perceptions were evaluated, revealing the blended learning group demonstrated superior learning effectiveness (d = 0.83) and reported higher deep learning perceptions (η2 = .05–.072) compared to the traditional learning group. These results provide valuable insights for educators aiming to design blended learning models that foster deep learning and improve overall learning effectiveness.